Association of Renal Functional Status in Different Stages of Diabetic Retinopathy - Chowdhury, Farah Diba; Omar Beg, Mirza; Chowdhury, Nusrath Jahan; Papri, Barsha Mojumder; Paul, Shukdeb (Medicine Today, 2025)
Introduction: Diabetic nephropathy (DN) and diabetic retinopathy (DR) are both complications of diabetic microangiopathy with similar pathogenesis and clinical relevance. Many studies have demonstrated an association between diabetic retinopathy and diabetic nephropathy in type 1 diabetes mellitus (T1DM) patients, but this association is less strong in T2DM. There is link exists between different stages of diabetic retinopathy and diabetic nephropathy in T2DM. Aims and Objective: To explore the renal functional status in different stages of diabetic retinopathy. Materials and Methods: This cross sectional study was conducted in the Department of Biochemistry, Sylhet MAG Osmani Medical College, Sylhet, Bangladesh during the period from July 2019 to December 2020. Forty hospitalized type 2 DM with retinopathy were selected. Previously diagnosed case of nephropathy, history of prolong intake of NSAID’S, patient with any acute condition like fever, heart failure, pregnancy were excluded. Serum creatinine, fasting blood sugar, HbA1c, creatinine clearance rate and urinary total protein were measured. Results: The mean age of the patients was 53.66 ± 13.51 years in non- proliferative and 56.21 ± 10.02 years in proliferative diabetic retinopathy; difference was not significant (p=0.538). The mean duration of diabetes was significantly greater in proliferative diabetic retinopathy compared to non- proliferative diabetic retinopathy (7.23 ± 2.86 years versus 11.36 ± 4.70 years; p=0.001). Raised serum creatinine [11 (42.3%) versus 7 (50.0%); p=0.641], decreased creatinine clearance rate [22 (84.6%) versus 14 (100.0%); p=0.278] and raised urinary total protein [21 (80.8%); p=1.000] did not significantly between non-proliferative and proliferative diabetic retinopathy. Conclusions: The renal functional status such as raised serum creatinine, decreased creatinine clearance rate and raised urinary total protein non-significantly greater in proliferative than no-proliferative diabetic retinopathy. Medicine Today 2025, Vol.37 (1): 114-118